The Role of User Satisfaction in Mediating Transaction Security and Customer Engagement on Loyalty in Using E-Wallet Services (Dana) - Shafira Marwah Alfiya; Agus Susanto (Takaza Innovatix Labs Ltd., 2026)
The rapid growth of digital payment systems has intensified competition among e-wallet providers, making user loyalty a critical challenge. This study examines the role of user satisfaction as a mediating variable in the relationship between transaction security and customer engagement on loyalty toward the DANA e-wallet service. The research was conducted using a quantitative approach, with data collected through questionnaires distributed to DANA users in Sumbawa City. A total of respondents were selected using purposive sampling, and the data were analyzed using Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results show that user satisfaction has a positive and significant effect on user loyalty. Transaction security and customer engagement both significantly influence user satisfaction, while their direct effects on loyalty are not fully consistent without the presence of satisfaction. Further analysis confirms that user satisfaction significantly mediates the effect of transaction security and customer engagement on loyalty. These findings indicate that loyalty toward e-wallet services is not formed solely through technical features or interaction intensity, but through users' evaluative experiences that lead to satisfaction. Transaction security creates a sense of trust and comfort, while customer engagement enriches user experience; However, both factors contribute to long-term loyalty only when they result in user satisfaction. This study highlights the strategic importance of prioritizing user satisfaction to transform secure systems and engagement initiatives into sustainable loyalty within digital financial services.